2020
DOI: 10.1016/j.ejmech.2020.112200
|View full text |Cite
|
Sign up to set email alerts
|

True or false? Challenges and recent highlights in the development of aspirin prodrugs

Abstract: Aspirin use is associated with severe gastrointestinal side-effects.• Identifying a true aspirin prodrug to overcome this limitation is challenging.• Mutual prodrugs of aspirin have been explored to reduce toxicity.• Mutual prodrugs of aspirin have been explored to enhance anti-cancer properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Furthermore, Liu et al found that arecoline can promote osteoblast differentiation and inhibit osteoclastogenesis [ 93 ]. Considering that osteoporosis and cardiovascular disease are common side effects caused by long-term aspirin treatment for inflammation [ 163 ], areca nut extracts are set to be developed into better drugs to treat inflammation and avoid or reduce side effects.…”
Section: Functional Effects Of Areca Nut Componentsmentioning
confidence: 99%
“…Furthermore, Liu et al found that arecoline can promote osteoblast differentiation and inhibit osteoclastogenesis [ 93 ]. Considering that osteoporosis and cardiovascular disease are common side effects caused by long-term aspirin treatment for inflammation [ 163 ], areca nut extracts are set to be developed into better drugs to treat inflammation and avoid or reduce side effects.…”
Section: Functional Effects Of Areca Nut Componentsmentioning
confidence: 99%
“…It has been a feature of about 1 in 20 drugs currently available on the legal market, with increasing number of prodrugs (1 in 8) in more recent years (Rautio et al, 2008; Rautio et al, 2018). Aspirin was thought to be a prodrug needing conversion to salicylate to be effective (Willetts & Foley, 2020; Wu, 2000). It was later discovered that acetylsalicylic acid itself is effective in disrupting prostaglandin synthesis (Willetts & Foley, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin was thought to be a prodrug needing conversion to salicylate to be effective (Willetts & Foley, 2020; Wu, 2000). It was later discovered that acetylsalicylic acid itself is effective in disrupting prostaglandin synthesis (Willetts & Foley, 2020). There is now considerable research into finding a true aspirin prodrug, which may reduce the known gastric effects of aspirin (Gaisina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is why many researchers adopted investigation of aspirin based-analogues as potential antitumor candidates [36] , [37] , [38] , [39] . Others considered conjugation of aspirin with antitumor chemotherapeutics [40] because inflammation initiated by cancer may lead to metastasis [41] . Furthermore, the reported antitumor properties of salicylamide-containing compounds [42] , [43] , [44] prompted the current study due to the targeted salicylamide derivative formed through conjugation of the carboxylic group of aspirin with the nitrogen atom of piperidinyl heterocycle.…”
Section: Introductionmentioning
confidence: 99%